2019
DOI: 10.3390/antiox8090374
|View full text |Cite
|
Sign up to set email alerts
|

Sweet Pepper (Capsicum annuum L.) Fruits Contain an Atypical Peroxisomal Catalase That Is Modulated by Reactive Oxygen and Nitrogen Species

Abstract: During the ripening of sweet pepper (Capsicum annuum L.) fruits, in a genetically controlled scenario, enormous metabolic changes occur that affect the physiology of most cell compartments. Peroxisomal catalase gene expression decreases after pepper fruit ripening, while the enzyme is also susceptible to undergo post-translational modifications (nitration, S-nitrosation, and oxidation) promoted by reactive oxygen and nitrogen species (ROS/RNS). Unlike most plant catalases, the pepper fruit enzyme acts as a hom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 93 publications
(155 reference statements)
2
48
0
Order By: Relevance
“…Figure 4 shows a simple model of the most important ROS metabolism enzymes modulated by NO PTMs. Catalase, exclusively present in peroxisomes, is negatively regulated by both nitration and S-nitrosation [168]. On the other hand, S-nitrosation, which inhibits O 2…”
Section: Regulatory Role Of No Ptms S-nitrosation and Nitration In Rmentioning
confidence: 99%
“…Figure 4 shows a simple model of the most important ROS metabolism enzymes modulated by NO PTMs. Catalase, exclusively present in peroxisomes, is negatively regulated by both nitration and S-nitrosation [168]. On the other hand, S-nitrosation, which inhibits O 2…”
Section: Regulatory Role Of No Ptms S-nitrosation and Nitration In Rmentioning
confidence: 99%
“…The profile of antioxidant enzymes during the ripening process has been investigated in pepper fruits previously but, to our knowledge, no comparisons have been made between varieties with different capsaicinoid contents. Thus, for example, in California-type pepper fruits, it has been reported that the catalase activity decreases as the fruit ripens [79,80] and this event is due to the post-translational modification (PTMs) underwent by the enzyme and promoted by ROS and reactive nitrogen species (RNS) derived from nitric oxide (NO) [41,81]. In fact, it has been proved that the ripening of pepper fruits is controlled by NO [8,40,80].…”
Section: The Ripening Stage and The Capsaicinoids Content Alter The Mmentioning
confidence: 99%
“…Relevant differences between the transcriptomes from green immature and ripe pepper fruits have been also reported, involving thousands of genes [8,40] and references therein. From a redox viewpoint, it has been found that reactive oxygen species (ROS) metabolism is also affected during fruit ripening, leading to major changes in total soluble reducing equivalents and the antioxidant capacity in fruits [41]. The profile of the major non-enzymatic antioxidants, including ascorbate, glutathione, carotenoids and polyphenols, has been followed during ripening in pepper fruits [4,11,12,[42][43][44][45][46], but less is known on how enzymatic antioxidants evolve with this physiological process.…”
Section: Introductionmentioning
confidence: 99%
“…The profile of antioxidant enzymes during the ripening process has been investigated in pepper fruits previously but, to our knowledge, no comparisons have been made between varieties with different capsaicinoid content. Thus, for example, in California-type pepper fruits it has been reported that the catalase activity decreases as the fruit ripens [80,81] and this event was due to posttranslational modification (PTMs) underwent by the enzyme and promoted by ROS and reactive nitrogen species (RNS) derived from nitric oxide (NO) [42,82]. In fact, it has been proved that ripening of pepper fruits is controlled by NO [8,41,81].…”
Section: The Ripening Stage and The Capsaicinoids Content Alter The Mmentioning
confidence: 99%
“…Relevant differences between the transcriptomes from green immature and ripe pepper fruits have been also reported, involving thousands of genes [8, 41 and references therein]. From a redox view, it has been found that the reactive oxygen species (ROS) metabolism is also affected during fruit ripening, leading to major changes in total soluble reducing equivalents in fruits and the antioxidant capacity [42]. The profile of the major non-enzymatic antioxidants, including ascorbate, glutathione, carotenoids and polyphenols, have been followed during ripening in pepper fruits [4,11,12,[43][44][45], but less is known on how enzymatic antioxidants evolve with this physiological process.…”
Section: Introductionmentioning
confidence: 99%